Ghosts of Machu Picchu [videorecording (DVD)] - Sechler, Craig (PBS, 2010)
"In the years since Machu Picchu was discovered by Hiram Bingham in 1911, there have been countless theories about this Lost city of the Incas, yet it remains an enigma. NOVA joins a new generation of archaeologists as they probe areas of Machu Picchu that haven't been touched since the time of the Incas and unearth burials of the people who built the sacred site"--Container.